Place of last drink enforcement: Effects on alcohol‐related traffic crashes. (27th December 2022) - Lenk, Kathleen M.; Toomey, Traci L.; MacLehose, Richard F.; Scholz, Natalie; Schriemer, Daniel; Nelson, Toben F.; Delehanty, Eileen; Bosma, Linda M.; Gloppen, Kari
Abstract: Background: Binge drinking can result in various types of harms including traffic crashes. Bars and restaurants that serve alcohol to patrons who are obviously intoxicated (i.e., overservice) contribute to these crashes. One strategy to address overservice is place of last drink (POLD) where law enforcement officers responding to alcohol‐related incidents inquire about where the individuals last drank alcohol. This information may then be used to identify bars and restaurants that frequently overserve alcohol. There is limited evaluation of the effectiveness of POLD in reducing overservice, traffic crashes, and other harms. Methods: We evaluated the effects of a POLD initiative, developed by some law enforcement agencies in Minnesota (USA), on alcohol‐related traffic crashes from 2010 to 2019. Among 89 intervention (POLD) vs. comparison communities, we fit regression models with participation in POLD as the predictor. As secondary analyses, we fit models with POLD implementation level as the predictor (implementation levels were assessed via a survey of law enforcement agencies). We controlled for relevant community and agency characteristics. Results: In the model with participation in POLD as a predictor, there was little difference in the rate of total alcohol‐related crashes (rate ratio [RR] = 1.07, 95% CI: 0.85–1.34). In the model with level of implementation as a predictor, the rate of total alcohol‐related crashes was comparable between communities with high implementation and those with no implementation (RR = 0.89; 95% CI: 0.71–1.10). Similar results were seen for alcohol‐related crashes with nonfatal injury and property damage outcomes. Conclusions: This study found little evidence that the POLD initiative, as currently implemented, was associated with reductions in traffic crashes across communities in Minnesota. Further research could explore whether specific characteristics of POLD are particularly important and whether POLD could be combined with other strategies to reduce traffic crashes and other alcohol‐related harms. Abstract : We evaluated whether a Place of Last Drink (POLD) enforcement initiative in Minnesota (USA), designed to reduce overservice of alcohol in bars/restaurants, had an effect on traffic crashes. We found little evidence that the POLD initiative, as currently implemented, was associated with reductions in traffic crashes; however, overall implementation levels were relatively low. Further research could explore whether POLD implementation can be improved and whether POLD could be combined with other strategies to reduce traffic crashes and other alcohol‐related harms.